FORMATION OF KNOWLEDGE AND SKILLS IN DESIGNING SPATIAL IMAGINATION IN STUDENTS IN ENGINEERING GRAPHICS CLASSES - Нурметов Мухтор Рустамович; Сейитниязова Айимхан Абдуллаевна (Web of Journals Publishing, 2025)
To consider methods and techniques aimed at improving spatial thinking in the process of teaching engineering graphics
Keywords: Education, engineering graphics, training, computer technologies, three-dimensional objects, efficiency, digital technologies, interactive methods, spatial thinking, practical significance, research.